Interaksi Bisnis dan Politik di Indonesia: Analisis Permasalahan dan Dampaknya terhadap Kebijakan Publik - Junita Mawartina; Agatha Cristy Siregar; Risma Nursuhayla; Kevin Immanuel Manurung (Lembaga Pengembangan Kinerja Dosen, 2024)
This study explores the interaction between business and politics in Indonesia, focusing on the issues arising from this relationship. Through secondary data analysis and literature review, this research finds that the close ties between business and political actors often trigger corruption, collusion, and nepotism (KKN), negatively impacting public policy and the economy. The results show that this relationship harms public interests and hinders governance quality. The study offers recommendations to address these issues to enhance transparency and accountability.